The Preparation and Reactions of Triphenyllead- and Triphenylgermanium Pentachlorophenoxides - Shahrezai Pakdaman, Ahmad; Fadayan, Manouchehr (Asian Journal of Chemistry, 2010)
The preparation of triphenyllead- and triphenylgennanium pentachlorophenoxides (C6H5)3PbOC6Cl5 and (C6H5)3GeOC6Cl5 are given along with their reactions with unsaturated substrates (C6H5N=C=O, S=C=S, O=S=O) which add across the M–O (M=Pb, Ge) bond of the alkoxides. The products have been identified and details of reactions discussed.